Notationen aus Zorn - Palme, Pia (My University, 2017)
This auto-ethnography explores wrath as a material and inspiration for my compositional practice, drawing on Donald W. Winnicott’s conception of a third space as an intermediary between the individual and the surrounding environment. Written for a lecture performance, the text compiles theoretical, practical, and poetic reflections about my process as a composer, performer, artist, and feminist. Rethinking listening as a tool to creatively interact with an environment, I propose that listening must be inclusive. As a listener, I explore the interior dimension of social interactions and my own inner space, my mind: thinking mind is an inner vocality. Composing is an intimate process that begins inside, progresses towards an ,outside’, and is well adjusted through the exchange with the environment. An important phase is the zone when an imagined sound becomes manifest as a notated image, to be further developed, performed, and perceived by an audience. I identify this time-space continuum as a third space linking my artistic process to a wider social context. Alongside my composition SETZUNG (2014), inspired by the work and life of the author Sor Juana Inés de la Cruz (Mexico 1651-1695), I look into aspects of veiling from artistic and cultural angles.
Auto-ethnographische Texte zu einer Performance über den Dritten Raum
Keywords: 700 Künste, Bildende und angewandte Kunst; 780 Musik